Project GENIUS: a challenge towards development of soft skills and competences valued by organizations - Morais, José Carlos; Podlaski, krzysztof; Monteiro, João Rocha (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
The project GENIUS, within the framework of the ERASMUS + Strategic Partnership for Higher Education program, involves the University of Lodz (Poland), Centria (Kokkola, Finland), Dundalk Institute of Technology (Ireland), and ISPGAYA (Porto, Portugal). The project is an intercultural and interdisciplinary challenge, were it’s aimed, in a short period of time, mentors and students create, develop and deliver informatics applications or other quality projects, under intensive rhythm of work.